Perioperative Management of Sectio Caesarea Surgery in Patient With Heart Valve Disorders - Purwoko Purwoko; Zidni Afrokhul Athir (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2021)
Cardiovascular disease in pregnancy is common range from 1% to 3 and contributes to 10-15% of maternal mortality. Valvular heart disease accounts for about 25% of cases of cardiac complications in pregnancy and important cause of maternal mortality, some of which are mitral stenosis and mitral regurgitation. Cesarean delivery remains the preferred choice, as it reduces the hemodynamic changes that can occur in normal delivery and allows for better monitoring and hemodynamic management. Our paper provide in-depth information regarding the pathophysiology of heart valve disease in pregnant women and an appropriate perianesthesia approach to obtain a good prognosis. We report a case of a 26-year-old pregnant woman, with obstetric status G1P0A0, 36 weeks’ gestation, body weight 61 kg accompanied by severe mitral regurgitation and moderate mitral stenosis. This patient was planned to undergo elective cesarean section. The patient's condition in the perioperative examination was: GCS E4V5M6, other vital signs within normal limits, SpO2 98-99% in supine position. Other physical and laboratory examinations were also within normal limits. The goal of anesthesia during surgery in patients with heart valve disease undergoing cesarean section maintain pulmonary capillary pressure to prevent acute pulmonary edema. In this case, regional anesthesia of epidural anesthesia was chosen because it can reduce systemic vascular resistance and provide better post-cesarean section pain. The patient's hemodynamics perianesthesia tended to be stable without any complications such as pulmonary edema.